2021
DOI: 10.18371/fcaptp.v2i37.229678
|View full text |Cite
|
Sign up to set email alerts
|

Banking in Digital Age: Efficiency of Аnti-Money Laundering System

Abstract: Abstract. The article is devoted to the problems of the development of a system for combating the legalization of income obtained illegally in the context of digitalization of banking activities. The concept of the effectiveness of the anti-money laundering system was considered. The expediency of using the utility approach for modeling the effectiveness of the system for combating money laundering has been determined. The indicator of the effectiveness of the system of combating money laundering was chosen as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Thus, scientists found that innovative inhibitors of the security of the country's financial sector are «growth of using online banking, improvement of internet user skills, expansion of activities online». Similar results were obtained by Leonov et al (2021). In particular, the researchers found that the development of FinTech innovations contributes not only to reducing the risks of disrupting the stability of the financial market but also acts as a guarantee of ensuring the state's economic security.…”
Section: Introductionsupporting
confidence: 70%
“…Thus, scientists found that innovative inhibitors of the security of the country's financial sector are «growth of using online banking, improvement of internet user skills, expansion of activities online». Similar results were obtained by Leonov et al (2021). In particular, the researchers found that the development of FinTech innovations contributes not only to reducing the risks of disrupting the stability of the financial market but also acts as a guarantee of ensuring the state's economic security.…”
Section: Introductionsupporting
confidence: 70%
“…Note that a pragmatic approach involves integrating technology to enhance compliance. Regulatory technology solutions can adeptly manage the substantial regulatory burden, ensuring more effective oversight (Day, 2021) and yielding innovative regulatory solutions (Lieonov, Vasylieva, Mynenko, & Dotsenko, 2021;Nikiforova & Nikiforov, 2021). Accordingly, these solutions not only deter illicit activities but also safeguard investors, preserving the financial system's integrity.…”
Section: Money Laundering and The Digital Agementioning
confidence: 99%
“…Econometric models help to carry out more in-depth studies, which are devoted to the transformational changes of economic systems at the macro level, resulting in the loss of balance in the financial sector. It was established that the money laundering system affects the macroeconomic stability of the country due to the increase in the shadow economy (Lyulyov O. et al, 2021;Sedmikova E. et al, 2021;Lieonov, S. et al Structural modelling for assessing the effectiveness of system for countering … Buszko A. 2022) especially in transition economies (Gamal, A.A.M.…”
Section: Literature Reviewmentioning
confidence: 99%